2014
DOI: 10.1371/journal.pone.0087948
|View full text |Cite
|
Sign up to set email alerts
|

Three Mitogen-Activated Protein Kinases Required for Cell Wall Integrity Contribute Greatly to Biocontrol Potential of a Fungal Entomopathogen

Abstract: Bck1, Mkk1 and Slt2 are three mitogen-activated protein (MAP) kinases constituting cell wall integrity (CWI) pathway that may control multi-stress responses via crosstalk with high-osmolarity glycerol (HOG) pathway in budding yeast. In this study, Bck1, Mkk1 and Slt2 orthologues in Beauveria bassiana were confirmed as the three-module cascade essential for CWI because cell wall impairment occurred in the hyphae and conidia of Δbck1, Δmkk1 and Δslt2 examined in multiple experiments. Strikingly, all the deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 45 publications
3
58
2
Order By: Relevance
“…In addition, the disruption of Mrhog1 or Mrslt2 leads to restricted vegetative growth and abnormal morphological clones on SMAY plates. This result was unlike the observations in ΔBbhog1 26 and ΔBbslt2 2728. Moreover, similar phenotypic changes have been observed in other fungi26272840, in which the single-gene disruptions increased sensitivity to cell wall damage, high osmolarity, and oxidative stress, as well as showing convoluted colonies.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…In addition, the disruption of Mrhog1 or Mrslt2 leads to restricted vegetative growth and abnormal morphological clones on SMAY plates. This result was unlike the observations in ΔBbhog1 26 and ΔBbslt2 2728. Moreover, similar phenotypic changes have been observed in other fungi26272840, in which the single-gene disruptions increased sensitivity to cell wall damage, high osmolarity, and oxidative stress, as well as showing convoluted colonies.…”
Section: Discussioncontrasting
confidence: 41%
“…This result was unlike the observations in ΔBbhog1 26 and ΔBbslt2 2728. Moreover, similar phenotypic changes have been observed in other fungi26272840, in which the single-gene disruptions increased sensitivity to cell wall damage, high osmolarity, and oxidative stress, as well as showing convoluted colonies. As in other fungi, these results indicated that the CWI and HOG pathways in M. rileyi could functionally overlap in responding to cell wall damage, osmoregulation, and oxidative stress171924.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Not too surprisingly, the ΔBbslt2 mutant showed defects in virulence using both topical and intrahemocoel injection assays. All three members of the B. bassiana CwI pathway, bck1, mkk1, and slt2, were further investigated (Chen et al 2014b). Single mutants of each gene generally resulted in similar phenotypes although some differences were noted.…”
Section: Map Kinase Pathwaysmentioning
confidence: 99%
“…To further confirm subcellular localization of Trr11 and Trr2 revealed by their eGFP-tagged fusion proteins, mouse monoclonal anti-eGFP antibodies (Cell Signaling Technology, Boston, MA, USA) were used to probe the fusion proteins in the protein extracts from the 3-day-old hyphal cultures of the WT and the selected transgenic strains following a protocol of Western blot hybridization described previously (Chen et al 2014). Briefly, the protein extract samples were separated through SDS-PAGE and transferred to ployvinyldene difluoride (PVDF) membranes (Millipore, Germany).…”
Section: Subcellular Localization Of Trr1 and Trr2mentioning
confidence: 99%